Pembangunan Bahan Dorong Ammonium Nitrat Untuk Roket Pepejal - Mohamad Nazri Mohd Jaafar; Wan Khairuddin Wan Ali; Shah Rizal Ruslan (PERINTIS eJournal, 2021)
The research focuses on the development of ammonium nitrate for use as oxidizer for solid rocket propellant. The development includes the production of propellant and its tests. All studies on the characteristics of ammonium nitrate were identified and recorded. Studies were also done on the fuel and binder materials. The fuel used is sulfur and aluminum. While some binders have been tested including glycol and resin. The developed propellant is produced using mold compression technique. Through this method, the produced propellant is more stable and uniform. The burning rate tests were performed at atmospheric pressure using propellant ingredient with varying oxidizer-fuel ratios. Through this, the optimum mixture ratio can be obtained. An analysis of static thrust was done using Propep software. Based on performance data obtained, it was found that the propellant has the potential to be further developed as solid rocket propellant.